면역친화성 컬럼을 이용한 특수용도식품 중 비타민B 12 와 비오틴 분석 연구 - 오보영; 예민지; 허수정; 이혜영; 방수진; Oh, Bo-Young; Ye, Min-Ji; Hu, Soo-Jung; Lee, Hye-Young; Bang, Soo-Jin (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2020)
This study was conducted to improve the standard method for vitamin B12 and biotin contained in foods for special dietary uses to ensure the specificity of the complex matrix properties of foods. For the food code, the test method was improved to determine vitamin B12 and biotin by high-performance liquid chromatography (HPLC)-UV using column-switching after concentration using immunoaffinity column. The immunoaffinity columns contain a gel suspension of monoclonal antibody specific to the vitamin of interest so that it can be used to concentrate the vitamin B12 and biotin and remove interferences from the food extracts. Moreover, validation of advanced new methods was carried out to support the suitability of the proposed analytical procedure (specificity, linearity, detection limits (LOD), quantitative limits (LOQ), accuracy, and precision). The improved analytical method is being used to monitor relevant food items on sale. The results of this study showed that the new analytical method is suitable and appropriate for managing food intended for special dietary uses. 본 연구는 특수용도식품에 함유되어 있는 비타민B12와 비오틴에 대하여 식품의 복잡한 매질 특성에 특이성을 확보할 수 있도록 현행 식품공전 시험법을 개선하고자 하였다. 식품공전에서 비타민B12와 비오틴의 시험법에 항체반응을 통해서 분석물질과 특이적으로 결합하여 그 외의 성분들을 효과적으로 제거할 수 있는 면역친화성 컬럼을 도입하여 시험용액을 정제 및 농축함으로써 전처리 과정을 개선하였다. 식품 등 시험법 마련 표준절차에 관한 가이드라인에 따라 밸리데이션(특이성, 직선성, 검출한계, 정량한계, 정확도, 정밀도)을 수행하고 개선된 시험법을 이용하여 유통 중인 특수용도식품의 대상 품목에 대해 시험법 적용여부를 확인하였다. 본 연구사업의 수행으로 시험·검사의 정확성을 증대시켜 특수용도식품 품질관리에 대한 신뢰성을 더 높일 것으로 본다.